Kondensiertes Glück? Komplexe Forschungsdesigns zur Entwicklung musikpädagogischer Interventionen - Birnbaum, Lisa; Flasche, Viktoria; Hasselhorn, Johannes; Jörissen, Benjamin; Kröner, Stephan; Lehmann, Andreas; Lill, Florian; Smolarczyk, Kathrin; Wießnet, Verena (Kulturelle Bildung. Theoretische Perspektiven, methodologische Herausforderungen und empirische Befunde, 2020)

Schwerpunktthemen der quantitativ-empirischen Forschung mit Bezug zur Digitalisierung in der kulturellen Bildung: Eine kartierende Forschungssynthese - Christ, Alexander; Smolarczyk, Kathrin; Kröner, Stephan (Zeitschrift für Erziehungswissenschaft, 2023)
In the context of the digital transformation, cultural activities have also changed. “Classical” activities have been digitally transformed, and new, genuinely digital activities have emerged. Many studies from various disciplines refer to this, which have not yet been adequately processed through research syntheses. Mapping reviews are suitable for providing an overview of the hot topics and desiderata of quantitative-empirical research at the intersection of digitization and cultural participation. In view of the large number of articles to be included, text mining including prioritized screening via predictive modelling is helpful. After screening n = 8500 potentially relevant papers from a database of n > 250,000 papers via predictive modelling, n = 3846 papers were included and mapped via topic modelling according to the investigated facets of cultural activities and overarching research themes. For the facets of cultural activities, a hot topic on video games was identified. For the overarching research themes, a variety of different topics emerged such as formal education in schools or motivation and flow. Regarding the methods chosen, it is discussed that these foci and desiderata across heterogeneous themes pave the way for topic-specific research syntheses as well as for further original research on the desiderata. Implications for the further development of the applied methods are discussed.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Cultural education; Digitalization; Research synthesis; Text mining; Topic modeling

The effects of setting and music on the intention to participate in out-of-school music classes: An experimental video vignette study - Smolarczyk, Kathrin; Wießnet, Verena; Birnbaum, Lisa; Kröner, Stephan (Psychology of Music, 2022)
There is a discrepancy between a high inherent value of extracurricular music classes and a low proportion of low-socioeconomic status (SES) male participants. However, evidence on how to match out-of-school music classes to students’ preferences is lacking. Thus, we assessed the attractiveness of different versions of such classes via an experimental video vignette study featuring a 2 × 2-factor (setting × music; each with high vs. low proximity to informal youth culture) between-subjects design with N = 244 students (Grade 5–10). We assessed the intention to participate as criterion, and gender, age, and SES (highest International Socio-Economic Index [HISEI] quartile) as control variables. A hierarchical regression showed a positive effect of music associated with youth culture on intention and no effect of the setting. Female (and older) students displayed higher intention than male (and younger) students. The single effect involving HISEI was a significant interaction of music and SES, which resulted from high-SES adolescents being especially motivated for classes with music associated with youth culture. Thus, to motivate boys and older students in particular, special consideration should be given to the appropriate design and marketing of music classes. However, music close to youth culture might be especially beneficial for adolescents with high rather than low SES.<br
Keywords: intention; music education; youth culture; vignette experiment; out-of-school

Two decades in the making: A scoping review on research on digital making and its potential for digital empowerment in non-formal settings - Smolarczyk, Kathrin; Kröner, Stephan (Journal of Research on Technology in Education, 2023)
FabLabs and makerspaces offer unprecedented opportunities for digital empowerment, especially for children and adolescents. However, reviews on making with regard to empowerment are lacking. We identified n = 180 publications on digital making with children and adolescents and, after categorizing them regarding formal criteria and formality of settings, identified the main topics in publications on digital making in non-formal settings. Results revealed a great demand for empirical studies with experimental designs. Three main topics emerged: domain-specific determinants of participation, equity, and skills and competencies. Implications for further research and limitations as well as implications for digital empowerment processes are discussed.
CRIS-Team Scopus Importer:2021-11-26
Keywords: children; digital empowerment; maker education; Maker movement; scoping review

Verortung der Förderrichtlinie DiKuBi und ihrer Vorhaben im Kontext der internationalen Forschung zur Digitalisierung in der kulturellen Bildung. In: Jörissen, B., Kröner, S., Birnbaum, L., Krämer, F. & Schmiedl, F. (2023). Digitalisierung in der kulturellen Bildung: Interdisziplinäre Perspektiven für ein Feld im Aufbruch. - Christ, Alexander; Birnbaum, Lisa; Smolarczyk, Kathrin; Kröner, Stephan (Digitalisierung in der kulturellen Bildung. Interdisziplinäre Perspektiven für ein Feld im Aufbruch, 2023)
Welche Konsequenzen und Potenziale bringt die digitale Transformation für die kulturelle Bildung mit sich? Antworten auf diese Frage bietet der vorliegende Band in Form einer Übersicht über Forschungsergebnisse aus dem BMBF-Förderschwerpunkt „Forschung zur Digitalisierung in der kulturellen Bildung“. Über mehrere Jahre hinweg haben darin 13 Verbund- und Einzelprojekte in ganz Deutschland zu digitalen Phänomenen in der kulturellen Bildung geforscht: zu Musik, Literatur, Tanz, Performance, bildender Kunst und darüber hinaus. Die Forschungsvorhaben zeichnen sich durch eine große Perspektivenvielfalt aus: Neben Erziehungswissenschaft und Bildungsforschung sind spezifische Sparten der kulturellen Bildung und weitere geisteswissenschaftliche Fächer ebenso vertreten wie die wie die Informatik. Zudem hat ein Metavorhaben qualitativ-metatheoretische Perspektiven entwickelt sowie Forschungssynthesen zur Digitalisierung der kulturellen Bildung insgesamt und zum digitalen Wandel einzelner kultureller Aktivitäten erarbeitet, teils unter Verwendung von Big-Data-Methoden. Die im Buch gebündelten Ergebnisse stellen eine wertvolle Ressource für Handelnde in Forschung, Kulturpädagogik und Politik dar, indem sie es ermöglichen, sich einen Überblick über das Innovationspotenzial zu verschaffen, welches sich aus der digitalen Transformation von kultureller Bildung ebenso ergibt wie aus ihrer Erforschung. (DIPF/Orig.)<br
Keywords: Kulturelle Bildung; Digitalisierung; Digitale Medien; Jugendkultur; Forschung; Bildung; Bildungsangebot; Inklusion; Mehrfachbehinderung; Partizipation; Anwendung; Soziales Netzwerk; Erwachsenenbildung; Lernumgebung; Musikunterricht; Musik; Musizieren; Musikwissenschaft; Medienpädagogik; Lernprozess; Kunstpädagogik; Ästhetische Bildung; Rezension; Bewertung; Bildungsprozess; Empirische Forschung; Deutschland